Đánh giá kinh tế các can thiệp vệ sinh ở Việt Nam : (The World Bank (WB), 2012)
This report is based on site reports and country data summaries prepared by field research teams in Cambodia, Indonesia and Vietnam. This report answers the questions: "Why a multi-country study of sanitation experience?" and "Findings and policy and strategy implications"